GMDSS manual global maritime distress and safety system (International Maritime Organization, 2013)
IMO IF970E GMDSS Manual, 2013 Edition The GMDSS Manual provides, in a single comprehensive publication, an explanation of the principles upon which the GMDSS is based, the radiocommunication requirements and recommendations for its implementation, the operational performance standards and technical specifications to be met by GMDSS equipment, and the procedures for and method of operation of the various radio services which form the GMDSS and the master Plan for the GMDSS. The 2013 edition is fully updated and includes: A description of the development and the concepts of the GMDSS A description of the components of the GMDSS, the carriage requirements and the operational procedures Excerpts from the relevant solas regulations for the GMDSS Supporting resolutions and circulars relevant to the GMDSS the IMO performance standards and related ITU-R recommendations giving the technical detail of the radio equipment The Joint IMO/IHO/WMO Manual on Maritime Safety Information (2010) The NaVTEX Manual (2012) The International SafetyNET Manual (2011) the current GMDSS Master Plan giving the details of the coastal infrastructure and services provided by member administrations Extracts from the ITU-R Radio Regulations giving the radio regulatory background. The Manual is intended for use by ship personnel, shore operators, trainers, administrations, regulators and anyone else concerned with ship communication.